Kinetic Study of Acid-Catalyzed Knoevenagel Condensation Between 5-Methoxy-1-Tetralone and Glyoxylic Acid - Michelle E. Herrera; Elvia V. Cabrera; Roger S. Guanoluisa; Ullrich Stahl (Chemistry Proceedings)
In this work we present, a kinetic study of the Knoevenagel condensation reaction between 5-methoxy-1-tetralone and glyoxylic acid, catalyzed by sulfuric acid, to produce (E)-2-(5-methoxy-1-oxo-3,4-dihydronaphthalen-2(1H)-ylidene)acetic acid. The reaction was carried out in a batch system at 400 rpm for 24 h at temperatures of 75, 80 and 85 °C. The yields obtained at these temperatures were 90.30, 93.75 and 94.16%, respectively. The reaction was monitored by TLC and HPLC. For the kinetic analysis, three mathematical methods were used: integral, differential and non-linear regression. The results showed an excellent fit of the experimental data to the pseudo-first-order kinetic model.